2017
DOI: 10.1016/j.eucr.2016.11.024
|View full text |Cite
|
Sign up to set email alerts
|

Sunitinib Enables a Clinical and Pathological Complete Remission of Metastatic Renal Cell Carcinoma (mRCC)

Abstract: Renal cell carcinoma (RCC) is the most common renal cancer, and has a poor prognosis in individuals with metastases (mRCC). In this report, we describe a 48-year-old woman with unresectable multiple liver metastases and a colonic metastasis of RCC who was treated with sunitinib in combination with hepatic microwave ablation and obtained a clinical and pathological complete remission. We consider that sunitinib combined with microwave ablation can prevent unresectable hepatic metastases of RCC from evolving, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
(5 reference statements)
0
1
0
Order By: Relevance
“…[110] And, within the context of LVM-RCC, MWA has been indicated to offer several practical benefits over other techniques, including a larger ablation volume, shorter surgical time, and a reduced heat-sink effect, without an increase in recurrence rate. [111] Moreover, the study by Peng et al has shown that the integration of sunitinib with MWA effectively prevents the progression of unresectable LVM-RCC, [112] suggesting that the combination of targeted pharmacotherapy with ablation technology holds potential for novel therapeutic avenues.…”
Section: The Site Of Rcc Metastasismentioning
confidence: 99%
“…[110] And, within the context of LVM-RCC, MWA has been indicated to offer several practical benefits over other techniques, including a larger ablation volume, shorter surgical time, and a reduced heat-sink effect, without an increase in recurrence rate. [111] Moreover, the study by Peng et al has shown that the integration of sunitinib with MWA effectively prevents the progression of unresectable LVM-RCC, [112] suggesting that the combination of targeted pharmacotherapy with ablation technology holds potential for novel therapeutic avenues.…”
Section: The Site Of Rcc Metastasismentioning
confidence: 99%